Some Convergence and Stability Results for the Kirk Multistep and Kirk-SP Fixed Point Iterative Algorithms - Gursoy, Faik F; Karakaya, Vatan; Rhoades, B. E. (HINDAWI LTD, 2014)
The purpose of this paper is to introduce a new Kirk type iterative algorithm called Kirk multistep iteration and to study its convergence. We also prove some theorems related to the stability results for the Kirk multistep and Kirk-SP iterative processes by employing certain contractive-like operators. Our results generalize and unify some other results in the literature.
Keywords: APPROXIMATION; CONSTRUCTION; MAPPINGS; THEOREMS; Mathematics